2000
DOI: 10.1029/1999wr900356
|View full text |Cite
|
Sign up to set email alerts
|

Karst Aquifer evolution in fractured, porous rocks

Abstract: Abstract. The evolution of flow in a fractured, porous karst aquifer is studied by means of the finite element method on a two-dimensional mesh of irregularly spaced nodal points. Flow within the karst aquifer is driven by surface recharge from the entire region, simulating a precipitation pattern, and is directed toward an entrenched river as a base level. During the early phase of karstification both the permeable rock matrix, modeled as triangular elements, and fractures within the rock matrix, modeled as l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(69 citation statements)
references
References 23 publications
1
62
0
1
Order By: Relevance
“…The method is inspired by speleogenetic process based models (Dreybrodt et al, 2005;Kaufmann and Braun, 2000). In order to accelerate the simulation, we use a proxy allowing to mimic the final result (mature system) without modeling the physical and chemical processes.…”
Section: Karst Conduit Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The method is inspired by speleogenetic process based models (Dreybrodt et al, 2005;Kaufmann and Braun, 2000). In order to accelerate the simulation, we use a proxy allowing to mimic the final result (mature system) without modeling the physical and chemical processes.…”
Section: Karst Conduit Simulationmentioning
confidence: 99%
“…The most advanced ones are based on modeling the physics and chemistry of the speleogenesis processes (Dreybrodt et al, 2005;Kaufmann and Braun, 2000). This approach allows understanding the kinetics of karst evolution, and give precious information about the speleogenesis processes.…”
Section: Introductionmentioning
confidence: 99%
“…Several sensitivity studies have evaluated the parameters in karst aquifers. Kaufmann and Braun (2000) reported that boundary conditions and sink recharges are important to the preferential flow path in a karst aquifer. Scanlon et al (2003) also confirmed that recharge is important to karst spring discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Individual fractures have been assembled into fracture networks in order to model patterns of evolving conduit systems (Lauritzen et al, 1992;Groves and Howard, 1994;Siemers and Dreybrodt, 1998;Kaufmann and Braun, 2000;Liedl et al, 2003). A typical benchmark setting emerged out of the Ewers's hardware models.…”
Section: Evolution Of a Discrete Network Under Pressurized Flow Condimentioning
confidence: 99%